Estratégias competitivas das empresas do setor hoteleiro de Curitiba diante das redes hoteleiras nacionais e internacionais - Ost, José Eldir (2007)
The phenomenon of the hotel chains in the city of Curitiba is going through a new phase by showing significant market losses due to the aggressive competition faced by the large domestic and international hotel chains with properties in the city. By taking this context into account, this study aims at examining the international influence on the local hotel chains and at understanding the innovation strategies adopted by the companies the hotel industry in the face of the competition, as well as at assessing the results of said strategies. The problem selected was: what are the innovation strategies adopted by the Curitiba hotel companies to face the competition posed by domestic and international hotel chains? In order to reach said goal, it was attempted at first to approach the new market context, globalization and technological innovation since those factors are responsible for the internationalization of the aforementioned market segment. Next, it was attempted to understand the strategies, the concepts and conceptions in order to place a new focus on the competitive strategies of the companies. The matters concerning services, innovations, strategies and outsourcing, the Brazilian and Curitiba hotel chains, indicators and performance have also been dealt with in detail. Finally and through a case study, it was possible to carry out an in loco investigation of three hotel companies in Curitiba, whose profiles, infrastructure and strategies were submitted to a critical analysis. Said analysis revealed that the scope of strategies and related to the Brazilian market represented a strategic asset that boosts business in this new environment in which the hotel chains are expanding.